International collaboration in information and communication technology of Malaysian scholars - Abu Bakar, Ahmad Bakeri; Junurham, Nur Leyni Nilam Putri (2013)
This paper is intended to study the pattern of scientific development in the Muslim world. For this purpose, Malaysian scholars were assessed with regard to their collaboration with scholars from the Muslim world. It was found that the main international collaborator among Malaysian scholars and institutions is Universiti Teknologi Malaysia (UTM) with 21 papers in all the three subject fields. The finding also illustrate that collaboration with those from Muslim countries is considered low. In order to improve collaboration between Malaysian scholars and scholars from the Muslim world, the government should promote bilateral, regional and multilateral programmes with countries in the Muslim world.